(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information on the relevance of improving the production technologies of food products with a balanced chemical composition, high nutritional and biological value, especially fermented milk products, enrichment of yogurt, which is one of the functional food products, with natural products and biologically active substances. Important chemical parameters that determine the specific useful properties and nutritional value of the extracted wheat grains are highlighted. The main goal of the research is to treat wheat flour with various non-conventional, in particular, ultra-high frequency electromagnetic fields in order to preserve the nutrients contained in wheat as much as possible. Also, the advantages of using malted wheat grains treated with ultra-high frequency electromagnetic field rays in the production of yogurt are explained. Conveniences of drying and using wheat malt collected by hydroponics method are provided. The optimal values of malt to be added to the composition of yogurt were determined, and the effect on important quality indicators of yogurt was studied. These fortified yogurts are said to help restore intestinal contractile function, thicken intestinal walls and restore elasticity and muscle tone.